The Drone Eats with Me: The Violent Intimacy of Life under Drones in Atef Abu Saif's Gaza Diary. - Brown, Sophia (Journal of War & Culture Studies, 2022)
This article analyses The Drone Eats with Me: A Gaza Diary (2015) by Atef Abu Saif, which documents Israel's military offensive against Gaza in 2014. It argues that the aesthetic choices Abu Saif makes are indicative of his status as a Palestinian author producing a work of testimony for a non-Palestinian readership. Written in English, the text clearly aims to persuade its readers of the challenges of life under the surveillance and targeting of drones, and the long-standing nature of Palestinian subjugation, especially in Gaza. By focusing on this mediation of Abu Saif's testimony – by both author and publisher – the article reflects on what is at stake when Palestinian narratives are produced for an Anglophone readership. It also demonstrates that Palestine's historical and socio-cultural context generates its own particular narration of drone warfare, conversant with other works of Palestinian literature.